Research on Drying Technology for Pressing Landscaping Waste - A case studay of Hibiscus rosa-sinensis flowers - Li Yingying; Chen Guoju; Li Juan (E3S Web of Conferences, 2024)
With the gradual enhancement of people's awareness of ecological environment and sustainable development, the concept of green and low-carbon development has received more and more attention. Building a waste recycling system has also become an important task for building a beautiful China. The art of pressed flowers is such an ecological industry for recycling abandoned landscaping plants. Hibiscus rosa- sinensis is a plant widely distributed and loved by the people in China. In order to explore the most suitable drying technology for pressing Hibiscus rosa-sinensis, we study the differences of petal color, anthocyanins content, pH value, enzyme activity, drying status, protecting color, flatness between no-pressed and two different drying methods. Compared with the fresh flowers, the L, a, and C values of dried petal were lower, the pH was higher, and the enzyme activity was lower. But the difference is not significant in anthocyanins content between them. Furthermore, the enzyme activity and pH value of pressed petal with microwave were lower than those with drying plate. On the contrary, the anthocyanins content of pressed petal with microwave was higher than that with drying plate. The final study data shows that microwave pressed flower with 80% microwave power and 60-second drying time, was better for drying Hibiscus rosa-sinensis than drying plate, this method leads to better pressed flower, so as to produce plant products that are more suitable for consumers' needs.